Wellbeing and quality of life assessment : a practical guide - White, Sarah C., editor; Abeyasekera, Asha, editor (Rugby : Practical Action Publishing, 2014)
Wellbeing and Quality of Life Assessment is a practical resource for people working in social or development policy and practice who are thinking about integrating wellbeing or quality of life in their work in both the global North and South. The main body of the book presents different tools that have been developed and used in social and development policy and practice, written by NGO professionals. These chapters outline the inspiration behind their approach, how it works, what has been learned through it, and issues and dilemmas that remain.